INTERNATIONAL SCIENTIFIC AND TECHNICAL CONFERENCE OF FOUNDERS AND METALLURGISTS - Ju. P. Bobrov (Литьë и металлургия)
Information about the International Scientific Conference in Minsk on May 19—21 2004 and Celebration of 50-th Anniversary of Cathedra "Machine and Foundry Production"